(untitled) (Namibian Journal for Research, Science and Technology, 2022)
The past three decades have been characterised by massive restructuring of public universities within Southern Africa. In line with the neo-liberal policy framework adopted in many countries, service provision in most public universities has become privatised and highly commercialised. As a result, outsourcing of support service functions to private service providers has become a widely entrenched feature of public universities in Southern Africa, reflective of the global trends. This has largely resulted in poor welfare for workers and escalating costs of service provision. Given the profit motive which is the primary driver for companies bidding for contracts to provide services in universities, the compromised welfare of workers and students will remain an ‘achilles heel’ of outsourcing. In this paper I argue that, the social enterprise can be adopted as a cheaper and effective alternative economic model to outsourcing in Universities